2014 IEEE 14th International Conference on Advanced Learning Technologies 2014
DOI: 10.1109/icalt.2014.52
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence Based Learning and Teaching Strategy for Computer Science Classrooms and Its Extension into a Mobile Classroom Response System

Abstract: Evidence-based instructional practices were incorporated in class, which gave immediate indication on student's problem solving skills and class participation information. This pedagogy showed positive results and broader acceptance by students in several semesters of intervention. Significant usage of mobile devices during class motivates the extension of this pedagogical approach of asynchronous problem solving using mobile devices. We believe that use of such devices in the classroom for solving interactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The findings [5] from that study and student's use of mobile devices during class time has encouraged us to developed this interactive problem solving teaching methodology. As several other [6]- [7] research works have shown that using technology during class can improve student's learning abilities, we are confident that the presented teaching tool will also have positive impact on student in-class engagement and problem solving skills.…”
Section: A Teaching Methodologymentioning
confidence: 89%
“…The findings [5] from that study and student's use of mobile devices during class time has encouraged us to developed this interactive problem solving teaching methodology. As several other [6]- [7] research works have shown that using technology during class can improve student's learning abilities, we are confident that the presented teaching tool will also have positive impact on student in-class engagement and problem solving skills.…”
Section: A Teaching Methodologymentioning
confidence: 89%
“…An IDE development environment for Android operating systems, it has an emulator to visualize the projects created. It contains C++ language and NDK tools that allow us to develop in native code [21].…”
Section: A Android Studiomentioning
confidence: 99%
“…In an effort to explore the feasibility of developing an integrated learning environment that supports automated and immediate assessment of construction exercises, we developed Mobile Response System (MRS) [8][9][10]. MRS is a software environment that facilitates in-class construction exercises and their real-time assessment utilizing mobile devices.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed design, implementation and deployment of the MRS system are out of scope of this paper. Interested readers are advised to explore MRS website [8] for downloadable modules and publications [9][10] to learn more. This paper explores MRS's support for engaging students via construction exercises and the Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%